The Influence Of Organizational Identification, Transformational Leadership And Employee Identification On Willingness To Cooperate In The Post-Acquisition Integration Phase At Grand Family Hospital - Cixo Cixo; Andry Andry; Sandra Dewi (Lembaga Pengembangan Kinerja Dosen, 2024)
Hospitals must be able to adapt quickly and develop the right strategy to survive, to become a large and strong hospital is one of them by carrying out an acquisition strategy. However, the post-acquisition integration phase process is the most critical stage that often makes the industry fail in managing human resources and can cause employee anxiety to employee resistance. This research aims to analyze the influence of organizational identification and transformational leadership on employee identification and willingness to collaborate, as well as employee identification on willingness to collaborate in the post-acquisition integration phase at Grand Family Hospital. This research is quantitative correlation research. The population is all 127 nurses who work at Grand Family Hospital. The sampling method was random sampling and 127 respondents were used. Data collection used a questionnaire with analysis techniques using path analysis. The research results show that organizational identification and transformational leadership partially influence employee identification and the willingness to collaborate, and employee identification influences the willingness to collaborate. Simultaneously, organizational identification, transformational leadership, and employee identification influence the willingness to collaborate. Hospitals need to pay attention to the relationship between organizational identification, transformational leadership, and employee identification simultaneously. Integrating strategies and policies that strengthen these three aspects together can create a work environment that supports and motivates employees to work together effectively. Organizational identification, transformational leadership and Worker Identification have a significant effect on the willingness to cooperate in the post-integration phase of the acquisition.